The Role of Strategic Orientation in Improving Innovative Capabilities - Amayali, Hakim Hsoonee; Banay, Laith Abdullah (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the current research is to uncover the role of strategic Orientation represented by (entrepreneurial orientation, marketing orientation and interactive orientation) In the creative capabilities represented by (Performance goals, personal innovation, learning goals, curiosity, and Innovation),Accordingly, the questionnaire tool was used In order to demonstrate the measurement of the level of availability of research variables in a sample Of the associate in the Diwaniya Roads and Bridges Directorate , In order to reveal the nature of the results that the research seeks to achieve, a set of statistical tools should be used (The normal distribution of the two types of Skewness and Kurtosis, structural modeling equation, Alpha Cronbach ,mean, and the standard deviation, Pearson correlation coefficient and regression coefficients was extracted by the program "AMOS.V.24),As the research seeks to clarify the relationship and role of the strategic direction in creative capabilities, Based on the results of the study, it was found that there is a correlation relationship and a significant effect of the strategic direction in creative capabilities. Perhaps the most important conclusions reached by the research were the contribution of the studied sample to the implementation of a series of projects that can generate profits describing the service of society, through invest these profits in the new investment mechanisms contribute to community service.